2019
DOI: 10.1111/ffe.13129
|View full text |Cite
|
Sign up to set email alerts
|

Crack closure in friction stir weldment using non‐linear model for fatigue crack propagation

Abstract: The fatigue crack propagation in a friction stir‐welded sample has been simulated herein by means of two 3‐dimensional finite element method (FEM)‐based analyses. Numerical simulations of the fatigue crack propagation have been carried out by assuming a residual stress field as a starting condition. Two initial cracks, observed in the real specimen, have been assessed experimentally by performing fatigue tests on the welded sample. Hence, the same cracks have been placed in the corresponding FE model, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The results showed that the maximum MCEPS contributes to a better prediction compared to the homogenized MCEPS. Noted that further validation with different values of stress triaxiality and Lode parameter is recommended. Further research is needed: (i) comparing the identified fracture strain exposed to multiaxial stress status with different uncoupled damage models, (ii) investigating the void number and positions effects on the identified fracture strain and (iii) using the proposed failure index to predict the ductile fracture of additively manufactured materials 42,43 and welded joints 44,45 …”
Section: Conclusion and Future Planmentioning
confidence: 99%
“…The results showed that the maximum MCEPS contributes to a better prediction compared to the homogenized MCEPS. Noted that further validation with different values of stress triaxiality and Lode parameter is recommended. Further research is needed: (i) comparing the identified fracture strain exposed to multiaxial stress status with different uncoupled damage models, (ii) investigating the void number and positions effects on the identified fracture strain and (iii) using the proposed failure index to predict the ductile fracture of additively manufactured materials 42,43 and welded joints 44,45 …”
Section: Conclusion and Future Planmentioning
confidence: 99%
“…In doing so, three cracks have been introduced into the MMC sample simulating the fatigue cracks propagation by means of both linear, ie, the Paris law, and non‐linear, namely, the modified Kujawski‐Ellyin (KE) or UniGrow laws. Non‐linear models for fracture mechanics can also assess the fatigue damage both at microstructural and macrostructural levels, which are based on the estimate of the energy release rate (ERR) for the prediction of fatigue crack propagation …”
Section: Introductionmentioning
confidence: 97%
“…Non-linear models for fracture mechanics can also assess the fatigue damage both at microstructural and macrostructural levels, which are based on the estimate of the energy release rate (ERR) for the prediction of fatigue crack propagation. [5][6][7][8]…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the so‐called local approaches allow a more realistic evaluation of the expected fatigue life 10–16 . In particular, among them, the authors consider in the present work the strain energy density (SED) method that, unlike other local approaches, like the notch stress intensity factor (NSIF) method, that allows to estimate the failure modes like, for example, weld root failure or weld toe failure 17 .…”
Section: Introductionmentioning
confidence: 99%